SAT0448 Report of 86 cases of congenital heart block: data from the italian registry (LU.NE REGISTRY). (12th June 2018) - Fredi, M.; Andreoli, L.; Bertero, T.; Bortoluzzi, A.; Breda, S.; Cappa, V.; Ceccarelli, F.; Cimaz, R.; Franceschini, F.; Gerosa, M.; Govoni, M.; Hoxha, A.; et al.
Abstract : Background: Cardiac neonatal lupus is due to placental transfer of maternal anti-Ro/SSA and anti-La/SSB autoantibodies to the fetus and mainly includes congenital heart block (CHB) and dilated cardiomyopathy. The prevalence of CHB has been estimated as 1%–2% in anti-Ro/SSA women while the recurrence rate is 16%–19%(. 1 This condition is associated with a high rate of fetal/neonatal mortality and in the majority of cases requires pacemaker pacing. 2–6 Objectives: The rarity of this condition requires the establishment of collaborative registries in order to improve our knowledge. Here we report the data of the ongoing Italian Registry of the autoimmune congenital heart block (Lu.Ne), which was created in 2016 Methods: The aim was to collect retrospective and prospective pregnancies complicated with CHB in patients with antibodies. Data regarding demography, treatment, maternal and neonatal outcome and follow-up were collected through an online electronic datasheet prepared in a Research Electronic Data Capture platform. Results: Eighty-six cases of CHB were collected in 82 women with 85 pregnancies that occurred between 1969–2016. CHB was mostly detected in utero (81 cases, 90.6%) with 5 neonatal CHB. Demographic description of the mothers, pregnancy outcomes and treatment are reported in table 1. Child mortality was observed in 22 (25.5%) cases: 12 fetal, 5 termination of pregnancy and 5 postnatal. Maternal and fetal risk factors for fetal mortality were analysed and, at univariate analysis, factors associated with death were an earlier detection of CHB (20.9±0.9 weeks vs 24.8±5.4 weeks; p=0.007), hydrops (p=0.002;OR=11.3;CI95%1.84–69.2) and pericardial effusion (p=0.025;OR >100;CI95%2.88->100). Conclusions: The Lu.Ne registry is an ongoing project aiming at collecting all Italian CHB. Our data showed similar rate of fetal/neonatal death and of PM implantation previously reported. We confirmed that hydrops and pericardial effusion are risk factors for fetal death. A peculiarity of our cohorts is that the majority of the mothers (59%) had an established diagnosis of systemic autoimmune disease at CHB detection. This is in contrast with other registries showing that usually CHB was incidentally detected in healthy women and related to the recruiting Centres all belonging to Rheumatology Society. The collection of cases from Gynaecological and Paediatric Centres, planned in the next months, will complete our analysis References: [1] Brucato, et al. Arth Rheum2001;1831–35. [2] Eliasson H, et al. Circulation2011;124:1919–26. [3] Izmirly PM, et al. Circulation2011;124:1927–35. [4] Levesque K, et al. Autoimmun Rev2015;14:1154–60. [5] Lopes LM, et al. Circulation2008;118:1268–75. [6] Van den Berg NW, et al. Int J Cardiol2016;225:167–171. Acknowledgements: This project was funded by Italian Society of Rheumatology Disclosure of Interest: None declared